EFFECTS OF ENVIRONMENT CONDITION ON THE POPULATION OF BRONTISPA LONGISSIMA GESTRO AND ITS PREDATOR CHELISOCHES SPP. IN NORTH LAMPUNG - Willy A. Baringbing; Bariyah Baringbing (International Coconut Community Journal, 1996)
A field study to investigate the effects of environment conditions on the population density of the coconut hispid Brontispa longissima Gestro and its predotor Forficulid Chelisoches spp. was carried out in Sin ar Saerang mandiri (SSM) coconut plantation and its surrounding area, North Lampung, in May 1993. 120 trees taken at random with 1,200 still folded leaflets in 4 locations, 300 palms each, in the SW garden were observed. Another 120 trees, also taken at random, in similar patterns as that of the S.W were studied. Chemical treatments were conducted regularly in the XSM area but none in the surrounding area. Results of the study showed that B. Longissma and its predator Chelisoches populations were found to be higher in the S.W.' garden than that of the surrounding coconut plantation. Those species of Chelisoches outside the garden and only one inside the area.